Dependency of Cholangiocarcinoma on Cyclin D–Dependent Kinase Activity. Issue 5 (1st July 2019) - Sittithumcharee, Gunya; Suppramote, Orawan; Vaeteewoottacharn, Kulthida; Sirisuksakun, Chumphon; Jamnongsong, Supawan; Laphanuwat, Phatthamon; Suntiparpluacha, Monthira; Matha, Arriya; Chusorn, Porncheera; Buraphat, Pongsakorn; Kakanaporn, Chumpot; Charngkaew, Komgrid; et al.
Abstract : Cholangiocarcinoma (CCA) is a bile duct cancer with a very poor prognosis. Currently, there is no effective pharmacological treatment available for it. We showed that CCA ubiquitously relies on cyclin‐dependent kinases 4 and 6 (CDK4/6) activity to proliferate. Primary CCA tissues express high levels of cyclin D1 and the specific marker of CDK4/6 activity, phospho‐RB Ser780. Treatment of a 15‐CCA cell line collection by pharmacological CDK4/6 inhibitors leads to reduced numbers of cells in the S‐phase and senescence in most of the CCA cell lines. We found that expression of retinoblastoma protein (pRB) is required for activity of the CDK4/6 inhibitor, and that loss of pRB conferred CDK4/6 inhibitor‐drug resistance. We also identified that sensitivity of CCA to CDK4/6 inhibition is associated with the activated KRAS signature. Effectiveness of CDK4/6 inhibition for CCA was confirmed in the three‐dimensional spheroid‐, xenograft‐, and patient‐derived xenograft models. Last, we identified a list of genes whose expressions can be used to predict response to the CDK4/6 inhibitor. Conclusion: We investigated a ubiquitous dependency of CCA on CDK4/6 activity and the universal response to CDK4/6 inhibition. We propose that the CDK4/6‐pRB pathway is a suitable therapeutic target for CCA treatment.